ISOLASI DAN IDENTIFIKASI SENYAWA METABOLIT SEKUNDER EKSTRAK METANOL DAUN KELOR (Moringa oleifera Lamk.) - Yuszda K. Salimi; Nurhayati Bialangi; Saiman Saiman (LPPM Universitas Muhammadiyah Gorontalo, 2017)
A study has been conducted on the isolation and identification of secondary metabolite compounds from methorol extract of kelor leaf (Moringa oleifera Lamk.). This study aims to isolate and identify secondary metabolite compounds from leaf kelur methanol extract. Moringa leaf was macerated with methanol and obtained a yield of 16.7% methanol extract. The extract of methanol separated by column chromatography yielded 272 fractions. The fraction was purified and analyzed by thin layer chromatography using eluent n-hexane: ethyl acetate (7: 3) and obtained stain spots with Rf (0.61) and (0.47). Phytochemical results of positive isolates on flavonoids test. The results of identification using UV-Vis spectrophotometry and infrared spectrophotometry is a flavonoid compound. The identification using UV-Vis spectrophotometry yields I absorbing bands at 250 nm wavelength. The absorption at 250 nm wavelength is suspected because of the non-bonding electron transition to the σ anti-bonding orbital (n → σ *) by an unconjugated ausochrome suspected to be a hydroxyl functional (OH) group. Identification using infrared (IR) spectrophotometry showed the presence of a bound OH function group, C = O, C = C aromatic, C-H aliphatic, C -O alcohol and = C-H aromatic. Telah dilakukan penelitian tentang isolasi dan identifikasi senyawa metabolit sekunder dari ekstrak metanol daun kelor (Moringa oleifera Lamk.). Penelitian ini bertujuan untuk mengisolasi dan mengidentifikasi senyawa metabolit sekunder dari ekstrak metanol daun kelor. Daun kelor dimaserasi dengan metanol dan diperoleh rendemen ekstrak metanol 16,7%. Ekstrak metanol dipisahkan dengan kromatografi kolom menghasilkan 272 fraksi. Fraksi dimurnikan dan dianalisis dengan kromatografi lapis tipis menggunakan eluen n-heksan:etil asetat (7:3) dan diperoleh bercak noda dengan Rf (0,61) dan (0,47). Hasil uji fitokimia isolat positif terhadap uji flavonoid. Hasil identifikasi mengunakan spektrofotometri UV-Vis dan spektrofotometri inframerah merupakan senyawa flavonoid. Identifikasi menggunakan spektrofotometri UV-Vis menghasilkan I pita yang menyerap pada panjang gelombang 250 nm. Serapan pada panjang gelombang 250 nm di duga karena adanya transisi elektron yang tidak berikatan ke orbital σ anti-ikatan (n→σ*) oleh suatu ausokrom yang tidak terkonjugasi yang diduga merupakan gugus fungsional hidroksil (OH). Identifikasi menggunakan spektrofotometri inframerah (IR) menunjukkan adanya gugus fungsi OH terikat, C=O, C=C aromatik, C-H alifatik, C−O alkohol dan =C-H aromatik.